Effects of ketamine and propofol on motor evoked potentials elicited by intracranial microstimulation during deep brain stimulation - Furmaga, Havan; Park, Hyun-Joo; Cooperrider, Jessica; Baker, Kenneth B.; Johnson, Matthew; Gale, John T.; Machado, Andre G. (Frontiers in Systems Neuroscience, 2014)
Few preclinical or clinical studies have evaluated the effect of anesthetics on motor evoked potentials (MEPs), either alone or in the presence of conditioning stimuli such as deep brain stimulation (DBS). In this study we evaluated the effect of two commonly used anesthetic agents, propofol and ketamine, on MEPs elicited by intra-cortical microstimulation of the motor cortex in a rodent model with and without DBS of the dentatothalamocortical (DTC) pathway. The effects of propofol anesthesia on MEP amplitudes during DTC DBS were found to be highly dose dependent. Standard-, but not high-, dose propofol potentiated the facilitatory effects of 30 Hz DTC DBS on MEPs. This facilitation was sustained and phase-dependent, indicating that, compared to high dose propofol, standard dose propofol has a beta-band excitatory effect on cortical networks. In contrast, ketamine anesthetic demonstrated a monotonic relationship with increasing frequencies of stimulation, such that the highest frequency of stimulation resulted in the greatest MEP amplitude. Ketamine also showed phase dependency but less pronounced than standard dose propofol. The results underscore the importance of better understanding the complex effects of anesthetics on cortical networks and exogenous stimuli. Choice of anesthetic agents and dosing may significantly confound or even skew research outcomes, including experimentation in novel DBS indications and paradigms.